2021
DOI: 10.1186/s40001-021-00481-2
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 promotes nucleus pulposus cell matrix degradation through regulating Nrf2/ARE axis

Abstract: Background This study aimed to assess the role and mechanism of lncRNA NEAT1 in intervertebral disc degeneration (IVD). Methods LncRNA profile (GSE56081) between IVD and healthy control was downloaded from the Gene Expression Omnibus (GEO) database and analyzes differential lncRNA expression. Expression of lncRNA NEAT1 in IVD tissue and TNF-α/IL-1β-stimulated nucleus pulposus cells were further measured by RT-PCR. The lncRNA NEAT1 overexpression pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Also, 11 widely regulated RNAs were screened. Of these, miR-185-5 P and NEAT1 have been shown to be associated with IDD progression ( Zhang H. et al, 2020 ; Li et al, 2021 ). The remaining genes have been shown to be involved in the pathological process of other diseases ( Ren et al, 2019 ; Tollenaere et al, 2019 ; Yang et al, 2019a ; Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, 11 widely regulated RNAs were screened. Of these, miR-185-5 P and NEAT1 have been shown to be associated with IDD progression ( Zhang H. et al, 2020 ; Li et al, 2021 ). The remaining genes have been shown to be involved in the pathological process of other diseases ( Ren et al, 2019 ; Tollenaere et al, 2019 ; Yang et al, 2019a ; Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“… 33 LncRNAs can induce EMT by regulating transcription factors such as E-cadherin, N-cadherin, vimentin, β-catenin, Snail, slug, etc., or alter the extracellular matrix (ECM) by changing the activity of ECM degrading enzymes (matrix metallopeptidase, MMP). 34 In addition, it can activate the Wnt/β-catenin, PI3K/AKT, MAPK and other signaling pathways, thereby promoting the invasion and metastasis of malignant melanoma. 35 A recent study reported the role of oncogenic lncRNA LNCOC1 in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…NP cells were first separated from the nucleus pulposus of human intervertebral discs. An IDD cell model was established by treating NP cells with IL-1β (5, 10, 20, 50 ng/ml) [17] or H2O2 (10,25,50, 100 μM) [18] for 24 hours. IL-1β (Order No.…”
Section: Culture and Treatment Of Cellsmentioning
confidence: 99%